The media and the military: Allies or adversaries? - Leopold Scholtz (Scientia Militaria, 2012)
Military commanders like Alexander the Great or Richard the Lionheart did not have to take public opinion greatly into account when they planned their campaigns in their day. Today it is a very different situation. In the light of the above this article starts with two somewhat startling quotes by the futurologists Alvin and Heidi Toffler: "The people thinking hardest about warfare in the future know that some of the most important combat of tomorrow will take place on the media battlefield." They also state: “[T]he media, including channels and technologies unimagined today, will be a prime weapon for Third Wave combatants in both the wars and anti-wars of the future, a key component of knowledge strategy.” In recent years, much has been made of the adversarial relations between journalists and the military. The media have, for instance, been blamed for the US defeat in Vietnam, for unthinkingly blabbing about tactical decisions in advance in the Falklands, etc. From their side, journalists have been blaming the military for not trying to understand the nature of their job, of covering up a number of bad things, etc.